Riga-Fede disease associated with emotional stress in the older child. - Hatice, Erdi Sanli; Esra, Yurumez; Ayse, Oktem; Nesrin, Ozben; Hale, Karadag (European Journal of Pediatric Dermatology, 2023)
Riga-Fede disease is characterized by benign inflammatory ulcerated lesions located on the ventral surface of the tongue, buccal mucosa, gingiva, or base of the tongue, resulting from repeated trauma. Although it is most commonly observed up to 1 year of age due to the traumatizing effect of the neonatal mandibular anterior teeth, Riga-Fede disease, as in this case, can occasionally occur in older children. Tongue biting is one of the causes of this disease in older children. A case in a 9-year-old girl was reported.